2018
DOI: 10.1007/978-3-319-89689-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Stress Granules and ALS: A Case of Causation or Correlation?

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by cytoplasmic protein aggregates within motor neurons. These aggregates are linked to ALS pathogenesis. Recent evidence has suggested that stress granules may aid the formation of ALS protein aggregates. Here, we summarize current understanding of stress granules, focusing on assembly and clearance. We also assess the evidence linking alterations in stress granule formation and dynamics to ALS protein aggregates and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 246 publications
0
47
0
Order By: Relevance
“…As for α‐Syn, we found that autophagy blockage by Atg5 knockdown increases PIC components in exosomes . Moreover, in a pathological context, amyotrophic lateral sclerosis is a neurodegenerative disease characterized by neurons presenting cytoplasmic aggregates whose formation is suspected to be facilitated by SG assembly . The prionoid TDP‐43 (transactive response DNA‐binding protein) is a nuclear RNA binding protein whose turnover and toxicity has been shown to depend on the endocytosis pathway .…”
Section: Exosomes and Homeostasismentioning
confidence: 87%
See 3 more Smart Citations
“…As for α‐Syn, we found that autophagy blockage by Atg5 knockdown increases PIC components in exosomes . Moreover, in a pathological context, amyotrophic lateral sclerosis is a neurodegenerative disease characterized by neurons presenting cytoplasmic aggregates whose formation is suspected to be facilitated by SG assembly . The prionoid TDP‐43 (transactive response DNA‐binding protein) is a nuclear RNA binding protein whose turnover and toxicity has been shown to depend on the endocytosis pathway .…”
Section: Exosomes and Homeostasismentioning
confidence: 87%
“…PICs contain stalled mRNA that can be reused to reinitiate translation upon stress release. If stress persists, SG clearance has been demonstrated to partly involve autophagy by a so‐called granulophagy mechanism . Interestingly, specific mRNAs have been shown to be the preferential targets of translational arrest, and were highly represented in a seminal paper describing exosomal mRNAs .…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic mutations are commonly observed in RNA-binding proteins such as FUS (e.g. R495X), and overexpression of some ALS-related mutant RNA-binding proteins results in the formation of aggregates enriched in canonical SG components such as G3BP1 and translation initiation factors [58,59]. We hypothesized that the formation of FUS R495X-mediated SG-like aggregates might also be suppressed by nsP3 ADPribosylhydrolase activity.…”
Section: Adp-ribosylhydrolase Activity Of Nsp3 Suppresses the Formatimentioning
confidence: 99%